Projecting the potential cost-effectiveness of dapagliflozin for chronic kidney disease in Kuwait. (31st December 2023) - Swidan, Ahmed; Elsisi, Gihan Hamdy; Ibrahim, Mohamed M.; Aljazzar, Mohammad; Tawfik Sallam, Hossameldin
Abstract: Introduction: In 2019, the prevalence of dialysis in Kuwait were 465 patient/million population, while the annual mortality rate among dialysis patients reached 12%. To improve resource allocation within the health care system, a cost-effectiveness model was conducted from a societal perspective to assess the cost-effectiveness of the use of dapagliflozin as an add-on-therapy against SoC (ramipril) among CKD patients with or without type-2 diabetes over their lifetime. Methodology: A Markov process model was utilized to assess the cost-effectiveness of dapagliflozin + ramipril versus ramipril alone on a cohort of patients with an eGFR of 25 to 75 mL/min/1.73, with or without type-2 diabetes and a urinary ACR of 200 to 5, 000 over their lifetime. The model included nine health states: (i) the six stages of CKD representing stages 1, 2, 3a, 3b, 4 and 5; (ii)ESRD, which represents RRT as dialysis or kidney transplant and (iii) death. Most of the clinical data were captured from the DAPA-CKD study. We assumed that the mortality risk of our study was similar to DAPA-CKD. The utility data were captured from different studies. Direct medical and indirect costs were captured from local data sources. Sensitivity analyses were conducted. Results: The difference in QALY between dapagliflozin + ramipril versus ramipril was 0.2. The difference in cost between the two arms was KWD −4, 120 (−USD25750). Dapagliflozin + ramipril generate better QALYs and lower costs than ramipril in CKD patients. Dapagliflozin improved the outcomes and generated cost savings in CKD patients. Conclusion: Adoption of dapagliflozin + ramipril is considered to be a cost saving option in addition to the improvement in QALYs in CKD patients with or without type-2 diabetes due to its nephroprotective effect, regardless of the aetiology of CKD, which eventually leads to reduction of dialysis and the transplantation cost burden on the Kuwaiti health care system. This study was focussed only on DAPA-CKD cohort.